2018
DOI: 10.1186/s13287-018-1065-0
|View full text |Cite
|
Sign up to set email alerts
|

Co-transplantation of mesenchymal stem cells improves spermatogonial stem cell transplantation efficiency in mice

Abstract: BackgroundSpermatogonial stem cell transplantation (SSCT) could become a fertility restoration tool for childhood cancer survivors. However, since in mice, the colonization efficiency of transplanted spermatogonial stem cells (SSCs) is only 12%, the efficiency of the procedure needs to be improved before clinical implementation is possible. Co-transplantation of mesenchymal stem cells (MSCs) might increase colonization efficiency of SSCs by restoring the SSC niche after gonadotoxic treatment.MethodsA mouse mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 47 publications
2
29
0
Order By: Relevance
“…RFP + MSC-derived pups were not observed. Indeed, also in our previous study, RFP + MSC-derived spermatogenesis could not be observed, although few MSCs coexpressed the germ cell marker MVH [21].…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…RFP + MSC-derived pups were not observed. Indeed, also in our previous study, RFP + MSC-derived spermatogenesis could not be observed, although few MSCs coexpressed the germ cell marker MVH [21].…”
Section: Discussionsupporting
confidence: 56%
“…It would have been interesting to evaluate the transplantation of TGFβ-treated MSCs alone. In our previous study [21], we included the transplantation of nontreated MSCs and showed that MSCs could help to restore endogenous spermatogenesis. Also, in the group transplanted with both SSCs and TGFβ-treated MSCs, endogenous spermatogenesis recovered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence has shown that transplantation of mesenchymal or endothelial cells into the testis interstitium or tubules, either before or 5 weeks after busulfan injection, can enhance the subsequent recovery of spermatogenesis from surviving endogenous stem cells 37‐40 . In the current study, a mixture of rhesus monkey testicular cells were injected into the irradiated testes, and it is likely that there are mesenchymal and endothelial cells present in the suspension, which might stimulate recovery of spermatogenesis from surviving endogenous SSCs.…”
Section: Discussionmentioning
confidence: 75%
“…This observation could be explained by the lower expression of genes involved in inflammation and cell migration in TGFβ1-treated MSCs, resulting in reduced lymphatic migration toward other organs. 140 SCs to restore fertility in the female…”
Section: Using Scs To Rescue Damaged Ssc Nichesmentioning
confidence: 99%